The Effectiveness of Tourist Hunting Project in Improving Students’ English Communication Skill - Kobis, Dewi Christa (OKARA: Jurnal Bahasa dan Sastra, 2019)
Language practice through direct communication will develop students’ English Communication Skills especially when they practice it with native English speakers. This study aims to find students’ level of interest in performing Tourist Hunting Project (THP) and the effectiveness of THP in improving students’ English Communication Skills (ECS). This study is a quantitative study by using SPSS 16 to calculate data from questionnaires and using Likert scale which is proposed by Pallant to interpret data. There are two types of questionnaires for this study. The first consisted of 5 questions to measure students’ level of interest in performing THP. Those were filled in by respondents before performing the THP while the second ones which consisted of 10 questions to measure the effectiveness of THP in improving students’ ECS were filled in after THP was performed by respondents as the requirement of passing a specific subject. The first finding showed point of 3.76 in the measurement of students’ interest in performing THP. This point is indicated as high based on a Likert scale. Thus, this study perceives that respondents were interested in performing THP. The second finding of this study showed the point of 3.65 which showed that the effectiveness of THP in improving students’ ECS is categorized high and respondents expressed positive attitudes towards THP in achieving their goals to improve their ECS.